2021
DOI: 10.1111/cpr.13172
|View full text |Cite
|
Sign up to set email alerts
|

Substrate stiffness regulates the differentiation profile and functions of osteoclasts via cytoskeletal arrangement

Abstract: Objectives Aging and common diseases alter the stiffness of bone tissue, causing changes to the microenvironment of the mechanosensitive bone cells. Osteoclasts, the sole bone‐resorbing cells, play a vital role in bone remodeling. This study was performed to elucidate the mechanism through which osteoclasts sense and react to substrate stiffness signals. Materials and methods We fabricated polydimethylsiloxane (PDMS) substrates of different stiffness degrees for osteocl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Moreover, the structure and the position of focal adhesions are inherently dynamic, which contribute to the reorganization of cell structure [ 167 ]. Positioned in the ECM proteins, Arg-Gly-Asp (RGD) sequences act pivotally in the process, which induce cellular responses through mechantransduction, including integrin signaling, focal adhesion organization, activation of cytoskeleton-associated molecules, calcium signaling and nuclear translocation of mechanosensitive transcriptional regulators [ 99 , 169 , 170 ].…”
Section: Effect Of Implant Surface Nanotopographies On Macrophages An...mentioning
confidence: 99%
“…Moreover, the structure and the position of focal adhesions are inherently dynamic, which contribute to the reorganization of cell structure [ 167 ]. Positioned in the ECM proteins, Arg-Gly-Asp (RGD) sequences act pivotally in the process, which induce cellular responses through mechantransduction, including integrin signaling, focal adhesion organization, activation of cytoskeleton-associated molecules, calcium signaling and nuclear translocation of mechanosensitive transcriptional regulators [ 99 , 169 , 170 ].…”
Section: Effect Of Implant Surface Nanotopographies On Macrophages An...mentioning
confidence: 99%
“…The stiffness of the extracellular matrix, a crucial mechanical cue, significantly impacts osteoclast behavior. Wang et al demonstrated that stiffer substrates (∼4 Mpa) upregulate osteoclast-specific markers and enhance bone resorption capabilities [ 81 ] ( Fig. 6 A).…”
Section: Engineering Approaches To Manipulate Osteoclast Behaviormentioning
confidence: 99%
“…56 On a soft PDMS matrix, the expression of RhoA and ROCK1/2 decreases in chondrocytes, 57 while the activation of cytoskeleton-related adhesion proteins and cascades of paxillin, FAK, PKC, and RhoA were detected in osteoclasts on the stiffer PDMS substrates. 58 RhoA/ROCK can not only respond to matrix stiffness but also act as intermediary molecules to mediate the cellular localization of YAP/TAZ. MSCs cultured in big fibronectin pattern have been found to entail the activation of the RhoA/ROCK signaling pathway and stimulate the formation of actin bundles, stress fibres and tensile actomyosin structures, which act as signals of the nuclear translocation of YAP/TAZ.…”
Section: Stiffnessmentioning
confidence: 99%